Influence of Social Media on Self-Esteem and Self-Awareness among 8th-grade Students - Hambul, Nulrahim J.; Balsani, Masmo S.; Mastul, Al-Rashiff Hamjilani (The Indonesian Institute of Science and Technology Research, 2025)
The primary aim of this research study was to investigate and analyze the influence of social media usage on self-esteem and self-awareness among 8th-grade students at Pangasinan National High School. It utilized a quantitative research design to determine the impact of social media on self-esteem and self-awareness among the respondents. The quantitative approach used a survey questionnaire checklist to collect the numeric data from the students. The result indicates that the most common platform, Facebook, has a range of 3 to 4 hours per day, with a frequency of 33, then the least common one is Snapchat, with a range of 1 hour or less, with a frequency. Self-esteem and Self-awareness levels of 8th-grade students were analyzed using Pearson, and the results obtained were interpreted to indicate that the correlation coefficient is equal to [0.58]. Based on the summary of findings from the study, it can be concluded that the levels of self-esteem and self-awareness as perceived by the 8th-grade students are moderate. Moreover, they point to the engagement of the students in social media in a way that enhances their self-image without becoming orderly and dependent on external validation. On the other hand, the students derive a large portion of their self-worth from online interactions, which may lead to heightened self-esteem or increased vulnerability to negative feedback.